2008
DOI: 10.3386/w14115
|View full text |Cite
|
Sign up to set email alerts
|

Naked Exclusion: An Experimental Study of Contracts with Externalities

Abstract: for their comments. We thank Tim Yuan for programming the software used in this study and Jamie Dana for his help in testing the software. The usual qualifier applies. The views expressed herein are those of the author(s) and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 0 publications
4
28
1
Order By: Relevance
“…Landeo and Spier (2008) find lower exclusion rates when contract offers are exogenous and when secret offers are permitted. They also note that communication decreases exclusion with non-discriminatory offers but increases exclusion with discriminatory offers.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Landeo and Spier (2008) find lower exclusion rates when contract offers are exogenous and when secret offers are permitted. They also note that communication decreases exclusion with non-discriminatory offers but increases exclusion with discriminatory offers.…”
Section: Introductionmentioning
confidence: 91%
“…Also, it has been shown that communication can decrease welfare with simultaneous discriminatory offers (Landeo and Spier, 2008) 21 Prior to imposing the $2.00 limit, one incumbent in treatment 2 charged $5.00 for signed buyers in an exclusion round. Throughout the paper, this price is treated as $2.00 instead of $5.00 to avoid distortion.…”
Section: Equilibrium Selectionmentioning
confidence: 99%
“…An incumbent monopolist can use DAC to achieve "naked exclusion" (Rasmusen et al, 1991). Landeo and Spier (2009) and Boone et al (2014) study experimentally how incumbent monopolist can use divide-and-conquer to achieve "naked exclusion." None of these studies, however, considers rich communication.…”
Section: Experimental Designmentioning
confidence: 99%
“…Our paper is the first to study exclusive dealing in an experiment with sequential contracting. Landeo and Spier [] report experimental evidence showing that the theoretical difference in exclusion rates between simultaneous discriminatory and simultaneous non‐discriminatory regimes is not that important from a behavioral perspective. In fact, when the buyers cannot communicate, the exclusion rate is not higher in a discriminatory than in a non‐discriminatory regime .…”
Section: Introductionmentioning
confidence: 99%